Evaluation in science teachers training - Furman, Melina Gabriela; Poenitz, María Verónica; Podestá, María Eugenia (Universidad Pedagógica y Tecnológica de Colombia, 2012)
This research analyzes the final evaluations of the major in Biology Teaching in an institution in northeastern Argentina. The evaluation circumstances were observed, and the professors were subsequently interviewed. The questions formulated by the professors in the test were analyzed according to the objective of their speech and the dimension of the evaluated sciences, by using the categories of science as a product (set of knowledge) and as a process (ways to know). 78% of the questions correspond to the category of science as a product compared to 22% as a process. Most of the formulated questions aimed to lowcomplex cognitive processes such as the enunciation of definitions or descriptions, and simple scientific skills as classifying. These results contradict professors’ concern about their students’ low level of reading comprehension and their stated objective of ‘teaching them to think’. This paper brings evidences as for the imperative need of strengthening the work with teacher trainers in learning evaluation aspects.